War and self-defense - Rodin, David (Clarendon Press, 2002)
When is it right to go to war? The most persuasive answer to this question has always been 'in self-defence'. David Rodin shows what's wrong with this answer. He proposes a comprehensive new theory of the right of self-defence which resolves many of the perplexing questions that have dogged both jurists and philosophers.